Kashi Vardaan: new okra variety - Sanwal, S K; Singh, B; Venkataravanappa, V; Halder, Jaydeep (Indian Horticulture, 2018)
Kashi Vardaan is a dark green fruited, high-yielding (150-160 q/ha) andresistant to yellow-vein mosaic virus (YVMV) and okra enation leaf curl virus(OELCV) variety. Moderately tolerant to major pest under field condition, it issuitable for both summer and rainy season. It is suitable for Uttar Pradesh,Bihar, Jharkhand and Punjab.